(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article identifies the speech place and role in the active thinking and schoolchildren mentality development in primary school lessons, its importance as a significant tool to raise and strengthen the schoolchildren knowledge level through linguistic and grammatical games.